Importance and Determination of Body Electric Current Pre and Post Feeding in Turkish Karayaka Sheep - Rıdvan Bayram; Hasan Çelikyürek; Hasan Koyun (Turkish Journal of Agriculture: Food Science and Technology)
Many scientific studies are conducted directly or indirectly with humans, animals, and plants. We believe that body electricity, which is generated and constantly present in the bodies of living beings, should be considered in scientific studies as an effective factor for production activity. We believe that body electricity should be included in the environment to bring the rumen fluids of sheep used in Daisy II rumen simulators closer to reality. In this way, the most realistic environment is created by adding the influencing factors of body electricity and many factors that can affect the outcome. The study was conducted on a total of 16 Karayaka ewes, including 4 lambs, 4 one-year-old ewes, 4 pregnant ewes and 4 lactating ewes. The data obtained in the study were collected by measuring the body electricity of the animals before and after grazing in 3 different periods for each group. At the end of the study, it was found that the value of body electricity of sheep determined at 0.12±0.001 v (volt) before feeding was higher than the value determined at 0.09±0.002 v after feeding. The difference between the two values was found to be statistically significant (P<0.05). However, it was found that the fact that the live weights of the animals in the groups were different and they were in different physiological periods did not cause a significant (P>0.05) difference in the electrical body currents before and after feeding (except in lambs (P<0.05)). It can be said that the measurements made in other periods and groups can change the electrical body currents after feeding and that the electrical body currents differ according to the animals fed in the barn, especially during the grazing period, before going to pasture and when returning to pasture.